Floristic diversity and degradation status of incense juniper (Juniperus thurifera L.) communities in the Aurès region of eastern Algeria - Abderrezek Lilya; Farhi Kamilia; Bachir Abdelkrim Si (Environmental & Socio-economic Studies, 2025)
In the Aurès region, Juniperus thurifera L. is a crucial part of the local ecological heritage. However, it is highly threatened and is mainly found in relict populations. The aim of this study was to assess the diversity and floristic richness of J. thurifera stands in the Aurès region of eastern Algeria. Surveys were carried out at four sites to improve our understanding of the plant taxa associated with J. thurifera and to assess the extent of this endemic species in this region. Through systematic sampling, we identified 83 species from 30 families and 70 genera, with Asteraceae and Fabaceae being the most dominant families at all sites. Several ecological parameters were analysed: Shannon's diversity index ranged from 4.72 to 5.63 bits. While Pielou's evenness index, ranging from 0.89 to 0.98, indicates a relatively high level of species diversity and even distribution within the plant communities. Analysis of the biological spectrum reveals a predominance of chamaephytes (32%), followed by hemicryptophytes (29%) and therophytes (27%). Disturbance indices indicate a higher anthropogenic influence at lower altitudes, ranging from 57% disturbance at Zana (1680 m) to 48% at Chélia (1993). The floristic composition is predominantly Mediterranean (66%). A study of hierarchical ascending classification (HAC) enabled us to differentiate four groups of plants, highlighting the incense juniper. These results provide a valuable baseline for monitoring changes in J. thurifera stands in response to climate variability and human pressures. Conservation and preservation efforts are imperative to prevent further degradation of this unique ecosystem.